Quality of Life Evaluation of Visegrad Group Compared with EU and Austria - Šanda, Martin; Křupka, Jiří (International Business Information Management Association-IBIMA, 2016)
This paper deals with the quality of life (QL) evaluation in Visegrad group and compared with European Union (EU) and Austria and progression of evaluation in years 2008 - 2014 based on official Eurostat methodology for QL evaluation - QL indicators for the EU. The data presented here come from several sources from within the European Statistical System (ESS), in particular Statistics on Income and Living Conditions (SILC), Labour Force Survey (LFS), European Health Interview Survey (EHIS), and administrative sources. The set is organised along the nine areas: Material living conditions, Productive or main activity, Health, Education, Leisure and social interactions, Economic and physical safety, Governance and basic rights, Natural and living environment, Overall experience of life. QL is evaluated by the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The countries of the Visegrad Group, EU and Austria are evaluated by TOPSIS for each year and the result is a ranking of QL countries. Next result is progress of this ranking countries in years 2008 - 2014.
Hodnocení kvality života Visegradské skupiny v porovnání s EU a Rakouskem
Keywords: indicators; quality of life; quality of life evaluation; TOPSIS; Visegrad group; ukazatele; kvalita života; hodnocení kvality života; TOPSIS; Visegradská skupina